Penyerapan Polutan Gas Co Dari Emisi Gas Cerobong Dengan Penyerap NaOH - Rofienda Rofienda; Siti Noer Tri H (Jurnal Kimia dan Kemasan, 2001)
CO gas from exhaust gas emzsszon industry in large quantities about I 000 ppm is dangerous for human health, if it inhaled through respiratory organ, nerve system and blood. Research has been done for catch the emission gas from exhaust gas use sodium hidroxyde solution as absorber and is sprayed by designed equipment. The result shown that percentage of CO gas absorbed by NaOH solution is direct indicate to concentration of absorber solution. NaOH solution I 000 mg/I can absorb CO gas up to 85,7%.